Aluminum-based diamond composite material and preparation method thereof

By plating W-Re-Ir diamond powder and aluminum alloy on the surface of aluminum diamond composite materials, and using rapid hot pressing sintering technology and magnetron sputtering method, the problems of poor material density, mechanical properties and thermal conductivity are solved. High-performance, low-cost preparation is achieved.

CN118895435BActive Publication Date: 2025-01-21SUZHOU HATENG TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411112729.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2025-01-21
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The existing aluminum diamond composite materials have poor density, mechanical properties, thermal expansion coefficient and thermal conductivity, and the interface bonding is not tight enough, resulting in unstable performance, high preparation cost and low efficiency.

Method used

Surface-coated W-Re-Ir diamond powder and aluminum alloy are used for ball milling, and then sintered in FHP rapid hot-pressing sintering equipment. The surface of the diamond powder is coated with a metal film using magnetron sputtering, and direct current is introduced during the sintering process. Field assisted sintering.

Benefits of technology

Significantly improve the density, mechanical properties, thermal conductivity and interface bonding strength of aluminum diamond composite materials, meeting the high performance requirements of electronic equipment heat sinks and substrates, while reducing preparation costs and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118895435B_ABST
    Figure CN118895435B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal-based composite materials, and discloses an aluminum-based diamond composite material and a preparation method thereof, which specifically comprises: optimizing and improving the formula of the aluminum-diamond composite material to adjust the thermal expansion coefficient of the aluminum-based diamond, and adopting different diamond particle gradations to ensure the density of the product; adopting a magnetron sputtering method to perform W / Re / Ir metal coating on the surface of diamond powder to improve the electrical conductivity and thermal conductivity of the diamond powder and enhance the adhesion with the aluminum-based material; in addition, combining a unique rapid hot pressing sintering technology to design a preparation process of the aluminum-diamond composite material, introducing a direct current electric field to assist sintering during the sintering process, so that the strength, rigidity and corrosion resistance life of the material are significantly improved; the aluminum-diamond composite material prepared by the invention has excellent performance and long service life, and can meet the requirements of contemporary packaging materials for high heat dissipation and high strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal-based composite materials, in particular to an aluminum-based diamond composite material and a preparation method thereof. Background Art

[0002] The electronic information industry is one of the leading and pillar industries in the development of the world economy today. As electronic devices develop towards high performance, high reliability and lightweight, power devices have put forward higher requirements on the performance of electronic packaging materials. The thermal conductivity of traditional electronic packaging materials is low and cannot meet the heat dissipation needs of electronic devices. Metal-based composite materials organically combine the good thermal conductivity and plastic deformation properties of the metal matrix with the lower thermal expansion coefficient and higher strength of the reinforcement to obtain electronic packaging materials with properties such as thermal conductivity and thermal expansion coefficient that are controllable within a wide range. Therefore, it is urgent to develop a new metal-based composite material to meet the increasingly high requirements of electronic packaging.

[0003] Compared with conventional aluminum and aluminum alloys, aluminum-based composites exhibit higher specific strength and larger specific modulus. This excellent performance is mainly due to the reinforcing body in the aluminum-based composite, which is usually a high-hardness ceramic. As a type of aluminum-based composite, diamond provides strong support for aluminum-based composites with its ultra-high hardness and good thermal stability. The dimensional stability of this composite is excellent, and its shape and size will hardly change even under high temperature or extreme environment. In addition, the thermal expansion coefficient of aluminum-diamond composites is small, which reduces the material damage caused by thermal stress. In addition to these basic properties, aluminum-diamond composites also show excellent fatigue resistance, fracture resistance and aging resistance. At the same time, aluminum-diamond composites also have excellent corrosion resistance, and can operate stably for a long time in harsh environments such as humidity, acid and alkali, extending the service life. In practical applications, aluminum-diamond composites are widely used in aerospace, automobile manufacturing, electronic and electrical fields, such as in the field of electronic and electrical equipment, they are widely used in heat sinks and substrates of electronic equipment. The corrosion resistance and aging resistance of this material make the shell and internal structure of electronic products more stable and reliable.

[0004] However, in practical applications in the fields of electronic packaging, the performance of aluminum-diamond composites is often unstable. This is mainly due to the weak interface bonding between aluminum and diamond, which easily leads to stress concentration and failure at the interface. The existing preparation process is costly and inefficient, and the density, thermal expansion coefficient and thermal conductivity of the prepared materials do not meet the new requirements of increasing development. In order to solve the above problems, researchers are constantly exploring new preparation processes and technical means, such as improving the performance stability of materials by optimizing the microstructure of aluminum-diamond composites and improving interface bonding; reducing preparation costs by developing new processing equipment and methods; and meeting the needs of large-scale production by improving preparation processes and improving production efficiency.

[0005] Due to the large differences in the physical and chemical properties of aluminum and diamond, the interface between the two is often not tight enough, which easily leads to interface failure of the material when it is stressed. In order to solve this problem, researchers can try to introduce surfactants or use special surface treatment techniques to improve the wettability and bonding between aluminum and diamond. In practical applications, aluminum diamond composite materials also need to consider their wear resistance, corrosion resistance and fatigue resistance. The improvement of these properties will help broaden the application field of the material and improve its stability and reliability in the actual working environment. In addition, the existing preparation process often has problems such as high energy consumption, long cycle and high cost, which is not conducive to the large-scale production and application of materials. Therefore, the present invention aims to explore new preparation technologies to reduce costs, improve production efficiency, and further improve the comprehensive performance of composite materials. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an aluminum-based diamond composite material and a preparation method thereof, which solves the problems of poor density, mechanical properties, thermal expansion coefficient and thermal conductivity of the existing aluminum-diamond composite materials and insufficient interface bonding.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] The invention discloses a method for preparing an aluminum-based diamond composite material, comprising the following steps: by weight percentage, continuously ball-milling 50-60% of surface-plated W-Re-Ir diamond micropowder and 40-50% of aluminum alloy in a ball mill at 150-250 r / min for 5-8 hours, wherein the grinding balls are zirconium oxide balls and the ball-to-material mass ratio is (3-5):1, pre-pressing for 15-25 seconds at 100-160 MPa, placing the pre-pressed raw material powder in a graphite mold and placing it in a vacuum chamber of an FHP rapid hot pressing sintering device, using an electrode pressure head to hold both sides of the mold, applying pressure and heating the mold containing the powder with a direct current power supply, evacuating to 5-10 Pa, heating to 550-650° C. at a heating rate of 80-100° C. / min for sintering, cooling naturally after sintering, and demoulding to obtain the aluminum-based diamond composite material.

[0009] Furthermore, the sintering pressure is 70-100 MPa, and the sintering time is 10-30 min.

[0010] Furthermore, the particle size of the surface-coated W-Re-Ir diamond micropowder is any combination of 100 μm, 50 μm, 25 μm, 10 μm and 5 μm, and different proportions are used for particle grading among the particle sizes.

[0011] Furthermore, the preparation method of surface-coated W-Re-Ir diamond micropowder comprises the following steps:

[0012] Step (1), placing metal W powder, metal Re powder and metal Ir powder in a horizontal mixer, mixing at 1000-1500r / min for 5-10h, after mixing evenly, pressing and molding in a four-column hydraulic molding machine, then placing in a medium frequency induction furnace, evacuating to 250-350Pa, heating to 800-1000°C at 2-5°C / min, pre-burning for 2-4h, then heating to 2200-2500°C at 1-3°C / min, keeping warm for 6-9h, cooling with the furnace, and obtaining a W-Re-Ir alloy.

[0013] Step (2), using magnetron sputtering technology to coat the surface of diamond powder with W-Re-Ir film, using 10% NaOH and 30% HNO 3 The diamond powder was boiled in the solution for 25-40 minutes, washed with deionized water for 3-5 times, dried, placed on the heating table of the magnetron sputtering coating equipment, and subjected to ultrasonic vibration. The chamber was evacuated to 4-6×10 -3 Pa, heated to 180-220°C, using W-Re-Ir alloy as the target, using magnetron sputtering process to deposit W-Re-Ir coating on the surface of diamond micropowder, the film thickness is 20-200nm, the chamber temperature is room temperature, and the surface of W-Re-Ir coated diamond micropowder is obtained.

[0014] Furthermore, in step (1), the metal W powder is 100 parts, the metal Re powder is 10-15 parts, and the metal Ir powder is 1-5 parts by weight.

[0015] Furthermore, in step (1), the pressure of the pressing molding is 10-20 MPa and the time is 20-40 s.

[0016] Furthermore, in step (2), the process conditions of magnetron sputtering are: sputtering power of 140-160 W, palladium current of 0.4-0.6 A, working gas pressure of 0.3-0.5 Pa, and sputtering time of 20-40 min.

[0017] By adopting the above technical solution, the beneficial effects of the present invention are:

[0018] (1) Optimize and improve the formula of aluminum diamond composite materials, adjust the thermal expansion coefficient of aluminum-based diamond, and use different diamond particle grading to ensure the density of the product and limit the amount of pores, so as to meet the requirements of matching the thermal expansion coefficient with chips in the electronic and electrical fields.

[0019] (2) A W-Re-Ir alloy with good heat resistance and stability was prepared by powder metallurgy, and a W-Re-Ir metal coating was performed on the surface of diamond powder by magnetron sputtering. The metal W, Re and Ir have strong heat resistance and high strength. By using the effects of magnetic and electric fields in a high vacuum environment, the atoms on the metal target are ionized and sputtered onto the surface of the diamond powder to form a uniform and dense metal coating, which improves the interface bonding degree between diamond and Al and significantly improves the thermal conductivity. In addition, its excellent corrosion resistance is used to effectively prevent the corrosive medium in the external environment from corroding the substrate. At the same time, the metal coating on the surface of the diamond powder can prevent the carbonization of diamond and the generation of Al with Al during the sintering process. 4 C 3 , further enhancing its adhesion to the aluminum substrate, meeting the heat dissipation requirements of large-scale integrated circuits and chips.

[0020] (3) The preparation process of aluminum-diamond composite materials was designed by combining the unique rapid hot pressing sintering technology. DC electric field assisted sintering was introduced during the sintering process. The combined effect of sintering temperature, DC electric field assistance and pressure promoted the microstructure of the aluminum-based composite material to be arranged in a more compact manner, and the material had a higher degree of densification. At the same time, transient liquid phase sintering can infiltrate the grain boundaries, promote the rearrangement, sintering and diffusion of particles, and make the growth of grains and the migration of grain boundaries easier, which is beneficial to the discharge of pores and the densification of products. Shorter sintering time can form a fine-grained structure, which significantly improves the mechanical properties. The uniform and dense microstructure and good interface bonding significantly improve the thermal performance parameters of aluminum-based diamond materials.

[0021] (4) The aluminum-diamond composite material prepared by the present invention solves the problems of low density, mechanical properties, thermal expansion coefficient and thermal conductivity of the aluminum-diamond composite material and insufficient interface bonding. It can meet the requirements of heat sinks and substrates of existing electronic equipment and meet the urgent demand for high thermal conductivity and lightweight thermal management materials for heat dissipation of high-power devices in the aerospace field. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of the aluminum-based diamond composite material prepared in Example 1.

[0023] Figure 2 This is a SEM image of the aluminum-based diamond composite material prepared in Example 2.

[0024] Figure 3 This is a SEM image of the aluminum-based diamond composite material prepared in Example 3.

[0025] Figure 4 It is a schematic diagram of the principle of FHP rapid hot pressing sintering equipment. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] (1) 100 g of metal W powder, 12 g of metal Re powder and 3 g of metal Ir powder were placed in a horizontal mixer and mixed at 1300 r / min for 8 h. After being mixed evenly, they were pressed in a four-column hydraulic molding machine at a pressure of 15 MPa and a holding time of 35 s. Then, they were placed in a medium-frequency induction furnace, evacuated to 300 Pa, and pre-sintered at 900 °C at 4 °C / min for 3 h. Then, they were heated to 2400 °C at 2 °C / min and kept at that temperature for 8 h. The alloy was cooled in the furnace to obtain a W-Re-Ir alloy.

[0029] (2) Magnetron sputtering technology was used to coat the surface of diamond powder with W-Re-Ir film, and then 10% NaOH and 30% HNO 3 The diamond powder was boiled in the solution for 30 min, washed with deionized water for 4 times, dried, placed on the heating table of the magnetron sputtering coating equipment, and subjected to ultrasonic vibration. The chamber was evacuated to 5×10 -3Pa, heated to 200 ° C, using W-Re-Ir alloy as the target, the sputtering power is 150 W, the palladium current is 0.5 A, the working gas pressure is 0.4 Pa, the sputtering time is 30 min, W-Re-Ir coating is deposited on the surface of diamond powder, the film thickness is 200 nm, the chamber temperature is room temperature, and the surface of W-Re-Ir coated diamond powder is obtained.

[0030] (3) According to the weight percentage, 50% of the surface-coated W-Re-Ir diamond powder and 50% of the aluminum alloy were continuously ball-milled in a ball mill at 200 r / min for 6 h. The grinding balls were zirconia balls with a ball-to-material mass ratio of 5:1. The surface-coated W-Re-Ir diamond powder was selected from double-particle powders of 10 μm and 5 μm with a ratio of 5:1. The powder was pre-pressed at 120 MPa for 20 s. The pre-pressed raw material powder was placed in a graphite mold and placed in a vacuum chamber of a FHP rapid hot pressing sintering equipment. The electrode pressure head was used to hold both sides of the mold. A DC power supply was used to pressurize and heat the mold containing the powder. The mold was evacuated to 8 Pa and heated to 560°C at a heating rate of 90°C / min for sintering. The sintering pressure was 80 MPa and the sintering time was 15 min. The mold was naturally cooled and demolded to obtain an aluminum-based diamond composite material.

[0031] Example 2

[0032] (1) 100 g of metal W powder, 10 g of metal Re powder and 5 g of metal Ir powder were placed in a horizontal mixer and mixed at 1500 r / min for 5 h. After being mixed evenly, they were pressed in a four-column hydraulic molding machine at a pressure of 20 MPa and a holding time of 20 s. Then, they were placed in a medium-frequency induction furnace, evacuated to 250 Pa, and pre-burned at 800 °C at 5 °C / min for 4 h. Then, they were heated to 2200 °C at 3 °C / min and kept at that temperature for 9 h. The alloy was cooled in the furnace to obtain a W-Re-Ir alloy.

[0033] (2) Magnetron sputtering technology was used to coat the surface of diamond powder with W-Re-Ir film, and then 10% NaOH and 30% HNO 3 The diamond powder was boiled in the solution for 40 min, washed with deionized water for 3 times, dried, placed on the heating table of the magnetron sputtering coating equipment, and subjected to ultrasonic vibration. The chamber was evacuated to 6×10 -3 Pa, heated to 220 ° C, using W-Re-Ir alloy as the target, the sputtering power is 140 W, the palladium current is 0.6 A, the working gas pressure is 0.5 Pa, the sputtering time is 20 min, the W-Re-Ir coating is deposited on the surface of the diamond powder, the film thickness is 200 nm, the chamber temperature is room temperature, and the surface of the diamond powder coated with W-Re-Ir is obtained.

[0034] (3) According to the weight percentage, 55% of surface-coated W-Re-Ir diamond powder and 45% of aluminum alloy were continuously ball-milled in a ball mill at 250 r / min for 8 h. The grinding balls were zirconia balls with a ball-to-material mass ratio of 3:1. The surface-coated W-Re-Ir diamond powder was selected from double-particle powders of 25 μm and 5 μm with a ratio of 3:1. The powder was pre-pressed at 160 MPa for 15 s. The pre-pressed raw material powder was placed in a graphite mold and placed in a vacuum chamber of a FHP rapid hot pressing sintering equipment. The electrode pressure head was used to support both sides of the mold. A DC power supply was used to pressurize and heat the mold containing the powder. The mold was evacuated to 10 Pa and heated to 580°C at a heating rate of 80°C / min for sintering. The sintering pressure was 90 MPa and the sintering time was 20 min. The mold was naturally cooled and demolded to obtain an aluminum-based diamond composite material.

[0035] Example 3

[0036] (1) 100 g of metal W powder, 15 g of metal Re powder and 1 g of metal Ir powder were placed in a horizontal mixer and mixed at 1000 r / min for 10 h. After mixing evenly, they were pressed in a four-column hydraulic molding machine at a pressure of 10 MPa and a holding time of 40 s. Then, they were placed in a medium-frequency induction furnace, evacuated to 350 Pa, and pre-burned at 1000 °C at 2 °C / min for 2 h. Then, they were heated to 2500 °C at 1 °C / min and kept at that temperature for 6 h. The alloy was cooled in the furnace to obtain a W-Re-Ir alloy.

[0037] (2) Magnetron sputtering technology was used to coat the surface of diamond powder with W-Re-Ir film, and then 10% NaOH and 30% HNO 3 The diamond powder was boiled in the solution for 40 min, washed with deionized water for 5 times, dried, placed on the heating table of the magnetron sputtering coating equipment, and subjected to ultrasonic vibration. The chamber was evacuated to 4×10 -3 Pa, heated to 220 ° C, using W-Re-Ir alloy as the target, the sputtering power is 160 W, the palladium current is 0.4 A, the working gas pressure is 0.3 Pa, the sputtering time is 20 min, the W-Re-Ir coating is deposited on the surface of the diamond powder, the film thickness is 200 nm, the chamber temperature is room temperature, and the surface of the diamond powder coated with W-Re-Ir is obtained.

[0038] (3) According to the weight percentage, 65% of surface-coated W-Re-Ir diamond powder and 35% of aluminum alloy were continuously ball-milled in a ball mill at 150 r / min for 8 h. The grinding balls were zirconia balls with a ball-to-material mass ratio of 4:1. The surface-coated W-Re-Ir diamond powder was selected from three particle sizes of 100 μm, 50 μm and 5 μm, with a ratio of 1:3:1. The powder was pre-pressed at 160 MPa for 15 s. The pre-pressed raw material powder was placed in a graphite mold and placed in a vacuum chamber of a FHP rapid hot pressing sintering equipment. The electrode pressure head was used to hold both sides of the mold. A DC power supply was used to pressurize and heat the mold containing the powder. The mold was evacuated to 5 Pa and heated to 650°C at a heating rate of 100°C / min for sintering. The sintering pressure was 100 MPa and the sintering time was 30 min. The mold was naturally cooled and demolded to obtain an aluminum-based diamond composite material.

[0039] Comparative Example 1

[0040] According to the weight percentage, 50% of diamond powder and 50% of aluminum alloy are continuously ball-milled for 6 hours in a ball mill at 200r / min. The grinding balls are zirconia balls, and the ball-to-material mass ratio is 5:1. The diamond powder is a double-particle powder of 10μm and 5μm, with a ratio of 5:1. It is pre-pressed at 120MPa for 20s, and the pre-pressed raw material powder is placed in a graphite mold and put into a vacuum chamber of an FHP rapid hot pressing sintering equipment. The electrode pressure head is used to support both sides of the mold, and a DC power supply is used to pressurize and heat the mold containing the powder, and the vacuum is evacuated to 8Pa. The temperature is increased to 560℃ at a heating rate of 90℃ / min for sintering. The sintering pressure is 80MPa, the sintering time is 15min, and it is naturally cooled. After demolding, an aluminum-based diamond composite material is obtained.

[0041] Relative density test: According to Archimedes principle, the actual density of aluminum-based diamond composite material is measured by drainage method. 1 , theoretical density ρ 2 Calculated by the law of mixture, relative density = ρ 1 / ρ 2 ×100%; The theoretical density reflects the density of the internal bonding of the sample. The closer the relative density is to 1, the fewer internal defects the sample has and the better the interface bonding is.

[0042] Thermal expansion coefficient test: The thermal expansion coefficient of the aluminum-based diamond composite material was measured using a static thermomechanical analyzer.

[0043] Thermal conductivity test: The thermal conductivity of aluminum-based diamond composites was tested using a laser thermal conductivity analyzer. The test specimen was a cylinder with a size of

[0044] Mechanical properties test: The mechanical properties test was carried out using an electronic tensile testing machine. The size of the tensile specimen was 3mm×4mm×15mm, the size of the bending specimen was 3mm×3mm×8mm, the tensile rate was 0.5mm / s, and the bending rate was 0.3mm / s.

[0045] Table 1 Performance test of aluminum-based diamond composite materials

[0046]

[0047] The closer the relative density value is to 100%, the denser the material is, the fewer internal defects are, and the better the interface bonding is. The diamond surface in Comparative Example 1 is not treated with coating, and the interface bonding and debonding with the aluminum alloy are serious, and there are many internal defects in the material, so the relative density of the prepared composite material is low. In Examples 1-3, as the content of W-Re-Ir diamond powder coated on the surface increases, the selective interface bonding between diamond and aluminum alloy is effectively reduced, the material has fewer internal defects, and the relative density is higher.

[0048] The coefficient of thermal expansion is a physical quantity that measures the change in volume or length of an object when the temperature changes. Too high a coefficient of thermal expansion may cause the volume of the material to change too much when the temperature changes, which may affect the performance and stability of the material.

[0049] In the formula of the present invention, diamonds are all made of different particle gradations to ensure the density of the product and limit the amount of pores, so as to meet the requirements of matching the thermal expansion coefficient with chips in the field of electronic appliances, etc.; the surface of the diamond powder is coated with W-Re-Ir metal by magnetron sputtering, and the atoms on the metal target are ionized and sputtered to the surface of the diamond powder by using the effect of magnetic field and electric field in a high vacuum environment, forming a uniform and dense metal coating. This coating not only improves the electrical conductivity and thermal conductivity of the diamond powder, but also enhances its adhesion to the aluminum base, thereby improving the degree of interface bonding and significantly improving thermal conductivity.

[0050] FHP rapid hot pressing sintering technology is used to promote the sintering and densification of aluminum diamond composite materials under the action of target sintering temperature, DC electric field assistance and pressure, promote the rearrangement, sintering and diffusion of particles, and make the growth of grains and grain boundary migration easier, which is beneficial to the densification of the product and enhances the sintering effect. As the sintering temperature increases, the metal film can quickly diffuse to the gap between the aluminum matrix and the diamond particles to wet the interface between the two, which can effectively reduce the viscosity and surface tension of Al, so that it can better combine with the diamond particles. After cooling, the product is demolded and taken out, and surface treatment is performed to obtain a composite material with dense product and excellent performance.

[0051] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but as long as it is within the scope of the claims of the present application, it is protected by the patent law.

Claims

1. A method for preparing an aluminum-based diamond composite material, characterized in that: The preparation method comprises the following steps: by weight percentage, continuously ball milling 50-60% of surface-plated W-Re-Ir diamond micropowder and 40-50% of aluminum alloy in a ball mill at 150-250 r / min for 5-8 hours, the grinding balls are zirconia balls, and the ball-to-material mass ratio is (3-5):1, then pre-pressing for 15-25 seconds at 100-160 MPa, placing the pre-pressed raw material powder in a graphite mold and placing it in a vacuum chamber of an FHP rapid hot pressing sintering device, using an electrode pressure head to hold both sides of the mold, applying pressure and heating the mold containing the powder with a direct current power supply, evacuating to 5-10 Pa, heating to 550-650° C. at a heating rate of 80-100° C. / min for sintering, cooling naturally after sintering, and demolding to obtain an aluminum-based diamond composite material; The method for preparing the surface-coated W-Re-Ir diamond micropowder comprises the following steps: Step (1), placing metal W powder, metal Re powder and metal Ir powder in a horizontal mixer, mixing at 1000-1500 r / min for 5-10 hours, after mixing evenly, pressing and molding in a four-column hydraulic molding machine, then placing in a medium frequency induction furnace, evacuating to 250-350 Pa, heating to 800-1000° C. at 2-5° C. / min, pre-burning for 2-4 hours, then heating to 2200-2500° C. at 1-3° C. / min, keeping warm for 6-9 hours, and cooling with the furnace to obtain a W-Re-Ir alloy; Step (2), using magnetron sputtering technology to coat the surface of diamond micropowder with W-Re-Ir coating, boiling the diamond micropowder with 10% NaOH and 30% HNO3 solution for 25-40 minutes, washing it with deionized water for 3-5 times, drying it, placing it on the heating table of magnetron sputtering coating equipment, and performing ultrasonic vibration, and evacuating the chamber to 4-6×10 -3 Pa, heated to 180-220°C, using W-Re-Ir alloy as the target, using magnetron sputtering process to deposit W-Re-Ir coating on the surface of diamond micropowder, the film thickness is 20-200nm, the chamber temperature is room temperature, and the surface of W-Re-Ir coated diamond micropowder is obtained.

2. The method for preparing the aluminum-based diamond composite material according to claim 1, characterized in that: The sintering pressure is 70-100MPa and the sintering time is 10-30min.

3. The method for preparing the aluminum-based diamond composite material according to claim 1, characterized in that: The particle size of the surface-coated W-Re-Ir diamond micropowder is any combination of 100 μm, 50 μm, 25 μm, 10 μm and 5 μm, and different proportions are used for particle grading among the particle sizes.

4. The method for preparing the aluminum-based diamond composite material according to claim 1, characterized in that: In the step (1), by weight, the metal W powder is 100 parts, the metal Re powder is 10-15 parts, and the metal Ir powder is 1-5 parts.

5. The method for preparing the aluminum-based diamond composite material according to claim 1, characterized in that: The pressure of the pressing molding in step (1) is 10-20 MPa and the time is 20-40 seconds.

6. The method for preparing the aluminum-based diamond composite material according to claim 1, characterized in that: The process conditions of magnetron sputtering in step (2) are: sputtering power of 140-160 W, palladium current of 0.4-0.6 A, working gas pressure of 0.3-0.5 Pa, and sputtering time of 20-40 min.

7. An aluminum-based diamond composite material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of W-plated diamond / aluminum composite

    CN105886849A